APPLICATION OF MATHEMATICAL MODELING OF THE AIRCRAFT STRUCTURES STRESS STATE TO OPTIMIZE CORROSION DAMAGE REMOVAL - D. P. Saidzhanov; V. V. Efimov (Научный вестник МГТУ ГА)
During the long-term aircraft operation, corrosion damage occurs on the aircraft structure. This leads to reducing of construction strength, rigidity and durability. Due to this corrosion damage removal and paintwork restoration are performed during the maintenance operation. During the corrosion damage removal not only corrosion products, but the material partially untouched by corrosion are removed as well. As a result, the cross-sectional area is reduced. This causes the increase of the stresses and decrease of the construction strength, rigidity and durability. However, it is impossible to refuse the removal of corrosion damage, but it is possible to optimize the stripping area parameters. The purpose of this paper is to solve the problem by applying mathematical modeling of the aircraft structures stress state by using open source software based on a finite element method (FEM). For preprocessing (creating geometry of the model, meshing) such software as FreeCAD, Gmsh, SALOME can be used, for processing (computation) – Code_Aster, which is included in SALOME-MECA software, for post processing (calculations visualization) can be used Post-Pro, which is also a part of SALOME-MECA software. Before the conducting computational experiments on the topic of this study the adequacy of the above mentioned software was checked. For this, the test problem of stress concentration in a plate with a circular hole – Kirsch task – was solved. At the same time, it was possible to achieve inaccuracy not exceeding 3%, due to this the adequacy of the selected software was considered as sufficient for conducting computational experiments in order to solve the problem. A technique of optimizing the removal of corrosion damage in aircraft structures was developed. It was demonstrated on a specific example of optimization of a plate corrosion damage stripping. After removal of the corrosion damage the minimum of the effective stresses was chosen as a criterion for optimality of the stripping area. In order to generalize the obtained results, the concept of the relative parameter of stripping was introduced which is the ratio of the  stripping diameter to the depth of the corrosion damage. A number of computational experiments  showed that there was an optimal value of the relative parameter of stripping, where a minimum of stresses acting in the plate after stripping was realized thus providing for the maximum possible durability of the structure after repair.